2019
DOI: 10.21082/jlittri.v25n2.2019.108-124
|View full text |Cite
|
Sign up to set email alerts
|

INOVASI TEKNOLOGI DAN INOVASI KELEMBAGAAN MENDUKUNG KEBERLANJUTAN USAHATANI LADA DI KALIMANTAN TIMUR / Technology and Institution Innovation Supporting the Sustainability of Pepper Farming System in East Kalimantan

Abstract: <p>Pepper farming in East Kalimantan has faced many obstacles. It is shown by the decline in pepper production in the last five years and the pepper conversion. This condition will affect the sustainability of pepper farming in East Kalimantan, as one of the national white pepper centers. Consequently, it is important to analyze and to establish a technology and institutional innovations. The study aimed to: (1) measure and analyze the sustainability of pepper farming, (2) identify technology innovation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 9 publications
0
4
0
2
Order By: Relevance
“…However, they could not predict whether farmers will readily adopt sustainable agricultural technologies themselves. Apart from that, the results of a studied by Wahyudi, et al (2019) on the sustainability level of pepper farming showed that the result is 3.0062, in the good category, but with a very low value. The sustainability analysis of farming was done using weighting and rating methods and the data were collected in Kutai Kertanegara Regency, East Kalimantan in 2016.…”
Section: Literature Reviewmentioning
confidence: 94%
See 1 more Smart Citation
“…However, they could not predict whether farmers will readily adopt sustainable agricultural technologies themselves. Apart from that, the results of a studied by Wahyudi, et al (2019) on the sustainability level of pepper farming showed that the result is 3.0062, in the good category, but with a very low value. The sustainability analysis of farming was done using weighting and rating methods and the data were collected in Kutai Kertanegara Regency, East Kalimantan in 2016.…”
Section: Literature Reviewmentioning
confidence: 94%
“…However, they could not predict whether farmers will readily adopt sustainable agricultural technologies themselves. Agus Wahyudi, et al (2019) believe that pepper farming in East Kalimantan face many obstacles. It is shown by the decline in pepper production in the last five years and the pepper conversion.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Requirement System Tahap dimana menentukan kebutuhankebutuhan bagi seluruh elemen-elemen sistem, kemudian mengalokasikan beberapa subset dari kebutuhan-kebutuhan tersebut bagi perangkat. Gambaran sistem merupakan hal yang penting pada saat perangkat lunak harus berinteraksi dengan elemen sistem lain seperti perangkat keras (Wahyudi & Wulandari, 2019)…”
Section: Algoritmaunclassified
“…Inovasi teknologi merupakan suatu perkembangan yang diperlukan untuk diterapkan dalam pertanian intensif guna membangun usahatani. Teknologi yang diterapkan dari berbagai model pertanian yang digunakan oleh petani dalam usahataninya (Wahyudi & Suci Wulandari, 2019). Salah satu model yang diperlukan dalam pertanian intensif yaitu teknologi irigasi atau dapat memanfaatkan dari hasil curah hujan (Ochoa-Noriega et al, 2022).…”
Section: Landasan Teoriunclassified